Humor at the workplace : a case study of chat interaction in a maker community - Vuong-Nyberg, Hang (2020)
Makerspace is not simply a workplace, but also an environment where makers can make possible their ideas and together build the community aspect. This concept, also referred to as hackerspace, hacklab, hackerspace, is commonly a not-for-profit community. Keeping in mind the interest of unfolding the holistic concept of this organization and the mission to uncover the communication in this kind, the research answers two important questions: 1) What are the main characteristics of the makerspace, particularly in terms of online communication and the use of humor and 2) How is humor co-created using technology-mediated communication. The research applies a multimodal approach in order to describe and portray the dynamics of chat interaction of a team. First, ethnographic notes are provided for some background understanding about the organization. Second, the conversation analysis is utilized to analyze the selected humorous events in detail. The findings of the thesis provide understanding about technology-mediated communication of a makerspace and insights into how the humorous instances occur during the team chat. The study also finds out the role of humor as the creation of a subculture in online communication. The research contributes to the humor studies and encourage companies to create an atmosphere that fostering humor in order to improve worker’s well-being.